The costume of science-fiction films - Lima, Vitalina Alves de (2008)
Science-fiction movies have been going through an interesting period. Many of them have been the object of re-edited and colored versions and renewed acknowledgment. They’ve become cult movies. Fan clubs of the genre should have the credit for this revival. Many fashion designers have created unique costumes for these movies. It is a risky job to venture into predicting what we’ll be wearing. Some designers, the most talented ones, were able to pull it off because, being researchers of history, they’ve drawn inspiration from the epic movies of the past to imagine thecoming events. This article brings forward an archeological study of clothing designed for somewhere in the future.